Metabolic Reconfiguration Supports Reacquisition of Primitive Phenotype in Human Mesenchymal Stem Cell Aggregates. (26th October 2016) - Liu, Yijun; Muñoz, Nathalie; Tsai, Ang‐Chen; Logan, Timothy M.; Ma, Teng
Abstract : Spontaneous aggregation and the associated enhancement of stemness have been observed in many anchorage dependent cells. Recently, aggregation of human mesenchymal stem cells (hMSCs) in nonadherent culture has been shown to reverse expansion‐induced heterogeneity and loss of stemness and reprogram the hMSC to reacquire their primitive phenotype, a phenomenon that can significantly enhance therapeutic applications of hMSC. The objective of this study was to investigate the mechanistic basis underlying the connection between multicellular aggregation and stemness enhancement in hMSC by testing the hypothesis that cellular events induced during three‐dimensional aggregation on nonadherent substratum induces changes in mitochondrial metabolism that promote the expression of stem cell genes Oct4, Sox2, and Nanog . Our results show that aggregation changes mitochondrial morphology and reduces mitochondrial membrane potential, resulting in a metabolic reconfiguration characterized by increased glycolytic and anaplerotic flux, and activation of autophagy. We further demonstrate that interrupting mitochondrial respiration in two‐dimensional planar culture with small molecule inhibitors partially recapitulates the aggregation‐mediated enhancement in stem cell properties, whereas enhancement of mitochondrial oxidative phosphorylation in the aggregated state reduces the aggregation‐induced upregulation of Oct4, Sox2, and Nanog . Our findings demonstrate that aggregation‐induced metabolic reconfiguration plays a central role in reacquisition of primitive hMSC phenotypic properties. Stem Cells 2017;35:398–410 Abstract : Cartoon summary of the metabolic/molecular pathways interaction that takes places during human mesenchymal stem cells aggregate formation.